Measurement of the isolated di-photon cross-section in $pp$ collisions at $\sqrt{s}=7$ TeV with the ATLAS detector - ATLAS collaboration (3034 authors) (2011)
The ATLAS experiment has measured the production cross-section of events with two isolated photons in the final state, in proton-proton collisions at sqrt(s) = 7 TeV. The full data set acquired in 2010 is used, corresponding to an integrated luminosity of 37 pb^-1. The background, consisting of hadronic jets and isolated electrons, is estimated with fully data-driven techniques and subtracted. The differential cross-sections, as functions of the di-photon mass, total transverse momentum and azimuthal separation, are presented and compared to the predictions of next-to-leading-order QCD.